Hydroxycinnamic acids and curcumin production in engineered Escherichia coli using heat shock promoters - Rodrigues, Joana L. (2017)
Supplementary data associated with this article can be found, inthe online version, at http://dx.doi.org/10.1016/j.bej.2017.05.015.